Design of Measurement of Water Content with Capacity Method to Determine Old Categories to Save Tapioca Flour - Hidayatullah, Syarifuddin Aprian; Suciyati, Sri Wahyu; Pauzi, Gurum Ahmad; Surtono, Arif (Journal of Energy, Material, and Instrumentation Technology, 2022)
In this study, water content measurements were carried out using a physical method using a capacitive sensor. Measurement with these two methods aims to get the most efficient method for tapioca flour’s water content value. The samples used were six samples of tapioca flour from the way good factory. Each sample was measured using a thermogravimetric method and a capacitive sensor measuring instrument three times per sample. The measurement results produce a polynomial graph with a coefficient of determination of 0.9702. The graph shows that the higher the water content, the higher the value detected by the capacitive sensor. The thermogravimetric method used as a reference takes 6 hours to get results, and the physical method takes less than one minute. To compare measurements, measurements were made using the thermogravimetric method to measure the percentage of water content in tapioca flour. This study indicates that the physical measurement method with a capacitive sensor instrument requires a shorter time than the thermogravimetric method. And the higher the water content, the shorter the storage time.